Heat Shock Tolerance in Deschampsia antarctica Desv. Cultivated in vitro Is Mediated by Enzymatic and Non-enzymatic Antioxidants - Cortés-Antiquera, Rodrigo; Pizarro, Marisol; Contreras, Rodrigo A.; Köhler, Hans; Zúñiga, Gustavo E. (Frontiers in Plant Science, 2021)
Throughout its evolutionary history, the Antarctic biota has constantly faced low temperatures from the harsh climate of the Antarctic continent. Deschampsia antarctica Desv, the most successful colonizing species on the continent, has been able to tolerate these extreme conditions, due to its morphology and physiology adapted to extreme climate. However, the climate in Antarctica is changing much faster than the rest of the planet, with more frequent heatwaves, which in the summer of 2020 reach maximums of 18.4°C and 20.75°C. These temperatures can be considered a thermal shock for Antarctic plants. However, the population of D. antarctica is increasing in number and size along the Antarctic Peninsula as a result of warmer temperatures. The plastic response and biochemical mechanisms of tolerance to abiotic stress in D. antarctica are well known. In this work, the response of D. antarctica cultivated in vitro (14 ºC) were subjected to two thermal shock treatments of 23 and 35 ºC and the physiological and biochemical responses were evaluated. Our results show that D. antarctica cultivated in vitro is capable of tolerating heat shock treatments; without showing visible damage to their morphology, without changes to the oxidative state, and also to the photosynthetic performance. These tolerance responses are mainly mediated by the efficient role of the enzymatic and non-enzymatic antioxidant systems that maintain the redox balance during the temperature rise.